Efeito de agentes de controle sobre Euschistus heros (Hemiptera: Pentatomidae) na cultura da soja, em diferentes estádios fenológicos e estratos do dossel - Daniel, Jeferson Luis Aquino (2019)
Several species of pest insects at different stages of soybean development (Glycine max) are described as of economic importance, but during the stages of reproductive development, the presence of phytophagous bugs, mainly Euschistus heros. The management of this species is made difficult by the disordered use of insecticides, the low technology of the application of control agents, and the failure to use adequate management strategies. In this sense, the objective of this work was to evaluate the effect of different agents for the control of E. heros, in different layers of the canopy and different stages of phenological development of soybean. Three bioassays were used to evaluate the mortality of E. heros: by direct contact (bioassay 1), tarsal contact (bioassay 2) and by ingestion (bioassay 3), were developed in two sowing seasons, October 2017 and February 2018, in soybean crop, in a 3 x 2 x 7 trifactor scheme. Factor A consisted of three layers of the soybean canopy (upper, middle and lower), factor B at two stages of phenological development (R3 and R5), and factor C in seven treatments (T1: distilled water, T2: imidacloprido; T3: lambda-cyalotrin; T4: Metarhizium anisopliae; T5: Beauveria bassiana; T6: imidacloprido + Metarhizium anisopliae; e T7: imidacloprido + Beauveria bassiana). The experimental design was a randomized complete block, with sub-subdivide plots, with four replications. The synthetic chemical insecticide lambda-cyhalothrin caused mortality of E. heros through the action of direct contact and tarsal contact, not causing mortality by ingestion. The synthetic chemical insecticide imidacloprid caused mortality of E. heros through the action of direct contact and ingestion, applied alone or in association with entomopathogens, being the only one to present systemicity in the acropetal sense. The entomopathogenic fungi B. bassiana and M. anisopliae have no insecticidal effect of E. heros under field conditions. In treatments that caused mortality to E. heros, mortality rates were higher in the upper canopy stratum.